Peran Konseling Pastoral Dalam Pernikahan Anak Usia Dini Dibawah Umur 18 Tahun - Niskar Triheti Gea; Difly Praise Malelak; Etaning Putra Zai; Upi Yanti Gea; Fingka Sri Fornidian Hura (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Early Childhood (AUD) is a social being who is in the age range of 0-8 years, the same thing is also stated by NAEYC. Early childhood is usually called the "golden age" because children at this age experience very rapid cognitive development. In this study there are several cases that occur regarding marriage at this age and with the role of counseling the researcher hopes to guide the client so that the client can recover, here the function of the counselor himself is to help the counselee understand himself, help avoid problems, help overcome problems and help the counselee to obtain his defense.